Electromagnetic oscillations at the edge of the Uragan-3M plasma - Pashnev, V.K.; Tarasov, I.K.; Tarasov, M.I.; Sitnikov, D.A.; Tsybenko, S.A.; Pinos, I.B.; Stepanov, K.N.; Olshansky, V.V.; Shvets, O.M.; Sorokovoy, E.L.; Petrushenya, A.A.; Lozin, A.V.; et al. (Вопросы атомной науки и техники, 2013)
In the Uragan-3M torsatron the plasma is ICRF heated with the use of antennas of different types. The objective of this work is to study the electromagnetic wave propagation outside the plasma confinement volume and the effect of these waves on confined plasma behavior during RF-heating.